2020
DOI: 10.1111/1467-9604.12301
|View full text |Cite
|
Sign up to set email alerts
|

Developing students' mental health literacy through the power of sport

Abstract: This research is an evaluation of a six‐week mental health literacy programme, referred to as the Cambridge United Community Trust’s ‘Mind Your Head’ programme, which was delivered by sports professionals to secondary school students (11‐16) in Cambridge, England, during 2017–18. A Mental Health Literacy Scale was used to measure students’ knowledge of mental health issues pre‐ and post‐intervention. Statistical data from these surveys were analysed using an independent samples t‐test. Focus groups were held w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…After a general observation of the current population, every individual can experience more happiness, satisfaction, and self-esteem by improving their physical and mental health levels. Healthy physical and mental health can enhance their sense of happiness and life Published by Francis Academic Press, UK -56-satisfaction, improve their quality of life, and actively promote self-evaluation [15][16]. It can maintain physical and mental health to prevent various diseases, cardiovascular diseases and respiratory system problems.…”
Section: Importance Of Physical and Mental Healthmentioning
confidence: 99%
“…After a general observation of the current population, every individual can experience more happiness, satisfaction, and self-esteem by improving their physical and mental health levels. Healthy physical and mental health can enhance their sense of happiness and life Published by Francis Academic Press, UK -56-satisfaction, improve their quality of life, and actively promote self-evaluation [15][16]. It can maintain physical and mental health to prevent various diseases, cardiovascular diseases and respiratory system problems.…”
Section: Importance Of Physical and Mental Healthmentioning
confidence: 99%
“…Mental health literacy is the knowledge and belief that helps people recognize, deal with and prevent mental diseases, as an important factor to promote mental health, mental health literacy plays an important role in identifying mental diseases, reducing disease stigma, and improving the mental health level of individuals and the public. Research shows that college students with low mental health levels are prone to psychological diseases such as anxiety, depression, and post-traumatic stress disorder [1]. The Outline of Healthy China 2020 Plan emphasizes that colleges and universities should strengthen the construction of students' psychological service system, the mental health literacy of college students is listed as the outcome index of "mental health promotion activities".…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that young people often have similar MHL deficits as adults (Burns and Rapee, 2006;Jorm et al, 1997;Kelly et al, 2006). They have difficulty identifying mental disorders and their underlying causes, risk factors and protective factors, and have misconceptions about therapeutic interventions' effectiveness (Glazzard and Szreter, 2020). In general, young people have fairly positive attitudes about professional help; however, these attitudes are not always reflected in the preferences of help-seeking.…”
Section: Introductionmentioning
confidence: 99%